2015
DOI: 10.1115/1.4029594
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Equations for Natural Convective Heat Transfer From Two Inclined Vertically Spaced Narrow Isothermal Flat Plates

Abstract: Natural convective flow over narrow plates induces an inward flow near the edges of the plate causing the flow to be three-dimensional near the edges of the plate. This influences the heat transfer rate near the edges of the plate and is referred to as the edge effect. The primary objective of this paper is to numerically study this edge effect and the interaction of the flows over two inclined vertically separated narrow heated plates of the same size embedded in a plane adiabatic surface. The cases where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These studies encompass plates oriented at various angles facing upward or downward, causing the buoyancy force to have two components over the inclined plate. Natural convection heat transfer from a wide inclined plate has been investigated by many researchers, including [21][22][23][24][25][26][27], while natural convection heat transfer from a narrow inclined flat plate has been investigated by Kalendar and Oosthuizen [28][29][30]. Oosthuizen and Kalendar [28,29] experimentally and numerically studied natural convective heat transfer from an isothermally heated inclined narrow flat plate in the laminar flow regime.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies encompass plates oriented at various angles facing upward or downward, causing the buoyancy force to have two components over the inclined plate. Natural convection heat transfer from a wide inclined plate has been investigated by many researchers, including [21][22][23][24][25][26][27], while natural convection heat transfer from a narrow inclined flat plate has been investigated by Kalendar and Oosthuizen [28][29][30]. Oosthuizen and Kalendar [28,29] experimentally and numerically studied natural convective heat transfer from an isothermally heated inclined narrow flat plate in the laminar flow regime.…”
mentioning
confidence: 99%
“…Natural convection heat transfer from a wide inclined plate has been investigated by many researchers, including [21][22][23][24][25][26][27], while natural convection heat transfer from a narrow inclined flat plate has been investigated by Kalendar and Oosthuizen [28][29][30]. Oosthuizen and Kalendar [28,29] experimentally and numerically studied natural convective heat transfer from an isothermally heated inclined narrow flat plate in the laminar flow regime. Their results showed that the mean Nusselt number increases with decreasing width of the plate and is higher for a positive inclination angle than it is for the corresponding negative inclination angle.…”
mentioning
confidence: 99%